ECONOMETRIC MODELING METHODS IN INVESTMENT FINANCING - Muminova Makhbuba Abduvafoevna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides for the development, discussion, and conclusions based on the study of the specifics of the theoretical foundations of the development of sources and methods of financing investment projects in the national economy.